2019
DOI: 10.1021/acssuschemeng.8b05523
|View full text |Cite
|
Sign up to set email alerts
|

Green Solvent for the Synthesis of Linear α-Olefins from Fatty Acids

Abstract: Whereas transition-metal-catalyzed decarbonylative dehydration of fatty acids shows promise as a more sustainable route to α-olefins, the solvents used for this process have so far been toxic compounds such as N-methyl-2-pyrrolidone and 1,3-dimethyl-3,4,5,6-tetrahydro-2­(1H)-pyrimidinone. Here, potential greener solvents are surveyed, using the well-defined precatalyst Pd­(cinnamyl)­Cl­(DPEPhos) (1). In general, the superiority of aprotic and polar solvents for this process is striking. An analysis of the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…Indeed, when investigating the SMD solvent effect on the Pd(PPh3)2 catalyzed mechanism 81 by changing from the apolar protic solvent (butanoic acid, εr=2,9) to a aprotic polar solvent (DMA, εr=37,8), it was found that the cationic β-hydride elimination via [M6-7 + ] ‡ experiences a massive decrease in energy (from 66.7 kcal/mol to 34.6 kcal/mol) (Scheme 11). 83 The preferred pathway however was still found to be the neutral low-coordinated Pd complex via [M5-7 + ] ‡ , which barrier was reduced from 38. (dashed lines), starting from geometries reported for Pd(PPh3)2-catalyzed decarbonylative dehydration.…”
Section: The Solvent Effect On 1-alkene Formation and Isomerizationmentioning
confidence: 99%
See 4 more Smart Citations
“…Indeed, when investigating the SMD solvent effect on the Pd(PPh3)2 catalyzed mechanism 81 by changing from the apolar protic solvent (butanoic acid, εr=2,9) to a aprotic polar solvent (DMA, εr=37,8), it was found that the cationic β-hydride elimination via [M6-7 + ] ‡ experiences a massive decrease in energy (from 66.7 kcal/mol to 34.6 kcal/mol) (Scheme 11). 83 The preferred pathway however was still found to be the neutral low-coordinated Pd complex via [M5-7 + ] ‡ , which barrier was reduced from 38. (dashed lines), starting from geometries reported for Pd(PPh3)2-catalyzed decarbonylative dehydration.…”
Section: The Solvent Effect On 1-alkene Formation and Isomerizationmentioning
confidence: 99%
“…pivalic anhydride) may further disfavor this side reaction. 61,64,81,83 Scheme 6. Investigated pathways of substrate activation and oxidative addition.…”
Section: The Role Of the Anhydride Activationmentioning
confidence: 99%
See 3 more Smart Citations